ANALISIS REKAMAN VIDEO CCTV DENGAN TEKNIK ENHANCEMENT MENGGUNAKAN METODE NATIONAL INSTITUTE OF JUSTICE (NIJ) - Erick Irawadi Alwi; Siska Anraeni (Elkom: Jurnal Elektronika dan Komputer, 2024)
Crime and criminality are increasing by utilizing electronic and digital devices, such as CCTV (closed circuit television) security devices, smartphones, and other electronic devices that have video features, record and store perpetrator data. CCTV recording files are sometimes unclear, so video forensic software is needed to clarify the object so that it can be used as evidence in court. The method used in this research is the National Institute of Justice (NIJ) method and enhancement techniques to clarify the image frame objects of CCTV video recordings using Amped Five forensic image and video tools. The results of the analysis of the evidence concluded that they had succeeded in identifying the vehicle number plate of the alleged perpetrator by carrying out an enhancement process (improving the quality) of the image object. The enhancement process is carried out by utilizing the optical debluring feature of the amped five forensic video software, in settings by increasing the size from 1 to 2 and increasing the noise value from 0.0100 to 0.6310 so it looks clearer than before.